Neutrosophic κ-structures in an AG-groupoid - G. Muhiuddin; K. Porselvi; B. Elavarasan (Neutrosophic Sets and Systems, 2023)
An AG-groupoid is the midway between commutative semigroup and groupoid. The core structure of Flock theory is an AG-groupoid, which focuses on motion replication and distance optimization and has numerous applications in physics and biology. Unfortunately, in many cases, modelling real-world problems in domains like computer science, operations research, artificial intelligence, control engineering, and robotics can be risky. Different theories, such as fuzzy sets, intuitionistic fuzzy sets, probability, soft sets, neutrosophic sets, and others, have been created to deal with similar situations. In this paper, We define the notions of neutrosophic κ-ideal structures in an AG-groupoid and investigate their properties. We also obtain equivalent assertion of neutrosophic κ-ideals and product of neutrosophic κ-structures in AG-groupoid.